2008
DOI: 10.1038/eye.2008.348
|View full text |Cite
|
Sign up to set email alerts
|

The groningen longitudinal glaucoma study III. The predictive value of frequency-doubling perimetry and GDx nerve fibre analyser test results for the development of glaucomatous visual field loss

Abstract: Purpose To investigate whether frequencydoubling perimetry (FDT) and nerve fibre analyser (GDx) test results are able to predict glaucomatous visual field loss in glaucoma suspect patients. Methods A large cohort of glaucoma suspect patients (patients with ocular hypertension or a positive family history of glaucoma without visual field abnormalities at baseline) was followed prospectively for 4 years with SAP (HFA 30-2 SITA fast), FDT (C-20 full threshold), and GDx (version 2.010) in a clinical setting. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…38–42 The evidence of the role of imaging devices to predict visual field loss is conflicting. Several studies with up to eleven years of follow up showed promising ability to predict visual field loss among glaucoma suspects, 4348 and possibly also in glaucoma patients, 49 while several other studies reported rather poor predictive ability 2, 3, 9, 12, but none with follow up longer than six years. There are also indications that the agreement between visual field progression and progression in optic disc photographs may be better than that between optic disc photographs and automated imaging results.…”
Section: Discussionmentioning
confidence: 99%
“…38–42 The evidence of the role of imaging devices to predict visual field loss is conflicting. Several studies with up to eleven years of follow up showed promising ability to predict visual field loss among glaucoma suspects, 4348 and possibly also in glaucoma patients, 49 while several other studies reported rather poor predictive ability 2, 3, 9, 12, but none with follow up longer than six years. There are also indications that the agreement between visual field progression and progression in optic disc photographs may be better than that between optic disc photographs and automated imaging results.…”
Section: Discussionmentioning
confidence: 99%
“…Several other methods to combine structure and function in glaucoma have been described in the literature. [6][7][8][26][27][28][29] A previous study by Boland and Quigley described a different method to combine structure and function in a single index, based on the calculation of probability of abnormality for each point in the visual field and for each sector of the optic disc using confocal scanning laser ophthalmoscopy. 30 The method showed a better performance than the structural parameters evaluated by confocal scanning laser ophthalmoscopy, but had a performance only similar to visual field global indexes.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Although different structural and functional parameters have been shown to have predictive ability, few attempts have been made to apply a combination of these parameters to improve prediction of damage. 7,8 Due to the different characteristics of structural and functional tests, it is possible that a combined approach could perform better than the isolated use of structural or functional tests.…”
mentioning
confidence: 99%
“…Morphologic and functional tests are now commonly used together to diagnose glaucoma and to follow up glaucomatous patients (Heeg & Jansonius 2009; Horn et al. 2011).…”
Section: Introductionmentioning
confidence: 99%